2015
DOI: 10.1182/blood-2015-03-635292
|View full text |Cite
|
Sign up to set email alerts
|

New role for the (pro)renin receptor in T-cell development

Abstract: Key Points PRR deletion in T cells drastically reduces the number of peripheral and thymic CD3+ T cells. We identify multiple stages of thymocyte development that require PRR expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…PRR is a new component of renin angiotensin system (RAS) and has high affinity with prorenin and renin resulting in cleavage of angiotensinogen and signaling through the mitogen-activated protein kinase (MAPK) and Wnt/β-catenin signaling pathways [7]. Moreover, PRR is mainly expressed in kidney, heart, pancreas, brain, blood vessels, macrophages, T cells and granulocytes [810]. Although several studies have shown that PRR is involved in renal and heart pathophysiology such as diabetic nephropathy, kidney ischemic, cardiac fibrosis [11, 12], the role in pancreas remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…PRR is a new component of renin angiotensin system (RAS) and has high affinity with prorenin and renin resulting in cleavage of angiotensinogen and signaling through the mitogen-activated protein kinase (MAPK) and Wnt/β-catenin signaling pathways [7]. Moreover, PRR is mainly expressed in kidney, heart, pancreas, brain, blood vessels, macrophages, T cells and granulocytes [810]. Although several studies have shown that PRR is involved in renal and heart pathophysiology such as diabetic nephropathy, kidney ischemic, cardiac fibrosis [11, 12], the role in pancreas remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the years since its discovery, much effort has been directed toward the characterization of signaling pathways that are "controlled" by Atp6ap2. These include Wnt (25)(26)(27) and promyelocytic leukemia zinc finger (PLZF) (39) signaling, despite a lack of similarity between the respective in vivo models (21), and that employed concentrations of its "ligands" renin and (pro)renin were several orders of magnitude above circulating levels (16). Abnormal vacuolar phenotypes are evident upon conditional Atp6ap2 knockout from cardiomyocytes (19), podocytes (18,20), and hepatocytes (24).…”
Section: Discussionmentioning
confidence: 99%
“…Atp6ap2 was initially misnamed as the (pro)renin receptor (PRR), as it was thought to bind renin and contribute to the pathology of hypertension (15,16). Atp6ap2 has since been shown to be essential for cellular homeostasis in mice, as its knockout is embryonic lethal (17), while conditional deletion impairs the function of a variety of cell types (18)(19)(20)(21)(22)(23)(24). Its role in Drosophila and Xenopus development is also established (25)(26)(27).…”
Section: Significancementioning
confidence: 99%
“…39,40 Within the immune system, the PRR pathway is active in human monocytes and is required in T lymphocytes for their acquisition of peripheral T cell markers including CD4 and CD8 during thymic education. 41,42 Moreover, the PRR is expressed on both macrophages and T cells infiltrating the glomerulus during human crescentic GN, and renin-mediated induction of IL-6 and cyclooxygenase-2 in human mononuclear cells requires extracellular signal-regulated kinase 1/2 phosphorylation but not angiotensin receptor ligation. 43 These data support a new paradigm in which RAS components other than the effector molecule Ang II modulate inflammation in the target organ.…”
Section: Renin/proreninmentioning
confidence: 99%